Being and becoming Inuit in Labrador - Kennedy, John (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2015)
Longitudinal research enables discussion of some of the consequences of Aboriginal organizations and identity politics for the Inuit and mixed Inuit-European peoples of Labrador. Newfoundland and Labrador Indians formed the province of Newfoundland and Labrador’s first Aboriginal organization, soon followed by a second, Inuit organization. The mixed Inuit-European “Settlers” (or Kablunângajuit) of northern Labrador initially preferred the Indian organization but were pressured to join and later would dominate the Inuit organization. Moreover, under the 2003 Inuit land claim, Kablunângajuit would legally be considered Inuit. Further south, people of similar mixed Inuit-European ancestry who long denied their Aboriginal roots would organize as Metis. Concurrent with the more than 40 years of identity politics, summarized by this paper, were major international and regional socio-economic changes that saw people move from local to distant work, creating new contexts for identity management. The paper shows how identity politics has changed relations of power and identity, has increased the numbers of people who are legally Inuit or aspire to be so, and, more generally, empowers Aboriginal people to shape their future.